PERBANDINGAN EFEKTIVITAS KUNYIT KUNING (CURCUMA DOMESTICA) DAN KUNYIT PUTIH (CURCUMA MANGGA) TERHADAP PERTUMBUHAN BAKTERI STAPHYLOCOCCUS AUREUS - SHOFIYATUZZAHRA RIZQIPUTRI M. SIREGAR; CUT MOURISA (LP2MTBM MAKARIOZ, 2021)
Yellow turmeric (Curcuma domestica) and white turmeric (Curcuma mangga) contain curcumin, flavonoid, and essential oilthat are used in traditional medicine for bacterial infections. This study aims to determine the effectiveness of Curcumadomestica and Curcuma mangga in inhibiting the growth of S. aureus. Experimental research. Extraction by macerationusing ethanol 70%. Antibacterial activity test technique used disc diffusion method by measuring clear zone of Curcumadomestica extract and Curcuma mangga extract concentration 100% and compared with control groups. Data wasprocessed using Kruskal-Wallis test followed by Mann-Whitney test. In the test, the mean result of extract of Curcumadomestica 15,4mm, extract of Curcuma mangga 34,1mm, positive control (amoxicilin) 13,65mm, and negative control(aquadest) did not form clear zone with a value (p=0,00) which were found differences in inhibitory effect of each groups.Extract of Curcuma mangga produced the largest clear zone (p=0,00). Extract of Curcuma mangga is the most effective ininhibiting the growth of S. aureus.